Women Empowerment and Community Development in Katsina State: A Study of Daura Local Government Area - Mumuni , Nurain Abayomi; Abdulyakeen, Abdulrasheed (Kashere Journal of Politics and International Relations, 2024)
The study examines women empowerment and community development in Katsina State with focus on Daura L.G.A. Specific objectives was to identify the problems hindering women’s participation in community development in Daura L.G.A. The study adopts Liberal Feminism theory as the theoretical foundation of analysis. It seeks to describe the social world from the distinctive vantage points of women. Descriptive survey design was applied as the research design of the study. The result revealed that 41.3% of respondents believe that lack of government assistance has significantly hindered women's empowerment and community development. The majority (60%) believe cultural factors are the main reason for women's lack of participation in community development. The majority (60%) have contributed financially to development projects, while 33.3% have contributed materially. The study recommended that assist women to achieve economic viability through acquisition of literacy and other necessary skills and resources. In addition, gender empowerment strategies under these circumstances require structural systemic change and basic attitudinal and value change. The real empowerment of women requires a thorough going renewal of the political process on a democratic basis.